Resembling left ventricular false tendon in a father and his daughter - Kaplan, Abdullah; Güneş, Hacı Murat (Hindawi Ltd, 2018)
Left ventricular false tendons (LVFTs) are linear fibrous or fibromuscular bands stretching across left ventricular cavity. Although LVFTs have been associated with various heart pathologies and investigated embryologically and histologically, there is only one report in the literature connoting possible hereditary transmission of this entity. We reported a father and his daughter having similar types of LVFTs with regard to location and thickness. With this report, we will contribute in the literature in respect to potential genetic inherence of LVFTs.
WOS: 000460344500001
PubMed ID: 30627451
Keywords: Thrombus; Children; Bands